Case report: Rare novel MIPEP compound heterozygous variants presenting with hypertrophic cardiomyopathy, severe lactic acidosis and hypotonia in a Chinese infant - Wang, Ling; Lu, Pengtao; Yin, Jie; Xu, Kangkang; Xiang, Dandan; Zhang, Zhongman; Zhang, Han; Zheng, Bixia; Zhou, Wei; Wang, Chunli; Yang, Shiwei (Frontiers in Cardiovascular Medicine, 2023)
Background Mitochondrial intermediate peptidase, encoded by the MIPEP gene, is involved in the processing of precursor mitochondrial proteins related to oxidative phosphorylation. Only a few studies have shown that mutations in MIPEP can cause combined oxidative phosphorylation deficiency-31 (COXPD31), an autosomal recessive multisystem disorder associated with mitochondrial dysfunction. We report herein a rare case of an 8-month-old boy in China with hypertrophic cardiomyopathy (HCM), severe lactic acidosis, and hypotonia caused by novel MIPEP compound heterozygous variants. Methods Trio-whole-exome sequencing and copy number variation sequencing were performed to identify mutated genetic loci. Sanger sequencing and quantitative real-time PCR were used to validate the candidate single nucleotide variants and copy number variants, respectively. Results The proband was an 8-month-old boy with HCM, severe lactic acidosis, and hypotonia who died 2 months after his first admission. Two novel compound heterozygous variants, c.1081T > A (p. Tyr361Asn) and a whole deletion (Ex1-19 del), were found in the MIPEP gene, which were inherited from his healthy parents respectively. Additionally, his mitochondria DNA copy number was significantly reduced. Conclusion We are the first to report a patient with rare MIPEP variants in China. Our findings expand the mutation spectrum of MIPEP, and provide insights into the genotype-phenotype relationship in COXPD31.